2022
DOI: 10.1177/00912174211067335
|View full text |Cite
|
Sign up to set email alerts
|

Mental health comorbidity and youth onset type 2 diabetes: A systematic review of the literature

Abstract: Background Type 2 diabetes (T2D) is a burgeoning epidemic in children and adolescents. Adult T2D doubles the risk of depression and mental health comorbidity makes it more difficult to make the lifestyle, medication adherence and health behavior changes needed to optimize outcomes. There is limited research on the impact of depression and depressive symptoms on youth T2D. Methods A search of the literature in the last 10 years regarding youth with depression and T2D was conducted. Abstracts were screened by 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…This is due, in part, to exposure to psychosocial factors including adverse childhood experiences, poverty 173,174 and mental health disorders 175–180 . Mental health disorders are common among adolescents with T2D, 181,182 reducing quality of life and readiness to adopt regular daily PA 46 . For example, the odds of being ready to adopt new health behaviors (including daily PA) are ~14% lower for every unit increase in anxiety, depression, and emotional distress among adolescents with T2D 46 .…”
Section: Type 2 Diabetes and Exercisementioning
confidence: 99%
See 1 more Smart Citation
“…This is due, in part, to exposure to psychosocial factors including adverse childhood experiences, poverty 173,174 and mental health disorders 175–180 . Mental health disorders are common among adolescents with T2D, 181,182 reducing quality of life and readiness to adopt regular daily PA 46 . For example, the odds of being ready to adopt new health behaviors (including daily PA) are ~14% lower for every unit increase in anxiety, depression, and emotional distress among adolescents with T2D 46 .…”
Section: Type 2 Diabetes and Exercisementioning
confidence: 99%
“… 171 , 172 This is due, in part, to exposure to psychosocial factors including adverse childhood experiences, poverty 173 , 174 and mental health disorders. 175 , 176 , 177 , 178 , 179 , 180 Mental health disorders are common among adolescents with T2D, 181 , 182 reducing quality of life and readiness to adopt regular daily PA. 46 For example, the odds of being ready to adopt new health behaviors (including daily PA) are ~14% lower for every unit increase in anxiety, depression, and emotional distress among adolescents with T2D. 46 In contrast, adolescents with T2D who reported having more resilient characteristics, particularly a connection to others and a sense of mastery over their lives, were 5%–10% more likely to be in the action and maintenance stage of change.…”
Section: Type 2 Diabetes and Exercisementioning
confidence: 99%
“…A recent systematic review concluded that there is a paucity of research in mental health and youth with T2D. Available studies primarily focus on prevalence of depressive symptoms [30,31]. In the TODAY study at baseline 14.8% had clinically signi cant symptoms [32].…”
Section: Discussionmentioning
confidence: 99%
“…A population based Canadian study demonstrated that youth with T2D had a higher likelihood of having a mood or anxiety disorder before and after diagnosis compared to matched youth without diabetes and children with T1D [36]. A systematic review also showed that higher rates of depression were associated with lower social support [30]. Analysis of the TODAY cohort showed that clinically signi cant symptoms of depression in youth with type 2 diabetes were associated with lower adherence to medication [37].…”
Section: Discussionmentioning
confidence: 99%
“…There are few reports focusing on the mental health of children with T2D. 21 In the TODAY study, 15% of youth scored at or above the cutoff for clinically significant depressive symptoms using screening questionnaires at baseline. This is a rate similar to that reported in adolescents from the general US population without diabetes.…”
Section: Discussionmentioning
confidence: 99%